2016
DOI: 10.1590/1807-57622015.0274
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do profissionalismo em estudantes da área da saúde: uma revisão sistemática

Abstract: Professionalism has been intensely debated in the last decade on the global stage and especially in the USA, and has been recognized as a skill that should be developed by all health professionals.Objective: The aim of the present study was to assess professionalism among graduates of healthrelated courses on a worldwide scale. Methods: Systematic review following the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: The review found seven studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…Additionally, the author highlights the need for deeper investigation into the assessment environment [12]. A systematic review done by de Mendonça showed a significant improvement in communication with patients, health education, respect for the interdisciplinary team, confidentiality, and attitudes like compassion and respect for diversity following the interventions and field experiences [13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the author highlights the need for deeper investigation into the assessment environment [12]. A systematic review done by de Mendonça showed a significant improvement in communication with patients, health education, respect for the interdisciplinary team, confidentiality, and attitudes like compassion and respect for diversity following the interventions and field experiences [13].…”
Section: Discussionmentioning
confidence: 99%
“…Assim com essa base, prossegue-se para "mostrar como" e "faz" que se refere ao comportamento, técnicas e habilidades práticas. Observa-se uma avaliação positiva dos discentes para com o processo de profissionalização no ensino em saúde após intervenções e/ou experiências de campo, como observado em outros estudos (Mendonça et al, 2016).…”
Section: Cuidado Farmacêutico Na Fotoproteção | 227unclassified
“…Profissionalismo Médico (PM) é definido como a união do uso rigoroso de estratégias comunicacionais, conhecimento científico, habilidades psicomotoras, raciocínio crítico, conteúdos emocionais, valores ético-morais e reflexões oriundas da atuação laboral cotidiana visando beneficiar o indivíduo e a comunidade envolvida 8 , que se delineiam em comportamentos, atitudes e padrões humanísticos de boas práticas com a finalidade de conferir excelência à qualidade dos cuidados em saúde 9 . No Brasil, essa competência foi validada e estruturada no formato de Matriz por Porto 10 , sendo descrita como algo que não depende somente da cognição, pois considera que, para um profissional agir com PM, faz-se necessário o alinhamento das práticas de saúde às especificidades requeridas pelo ambiente de trabalho desse profissional.…”
Section: Introductionunclassified